Heavy metal contamination in retailed food in Bangladesh: a dietary public health risk assessment - Begum, Ruhena; Akter, Rahima; Dang-Xuan, Sinh; Islam, Shariful; Siddiky, Nure Alam; Uddin, ASM Ashab; Mahmud, Asheak; Sarker, Md Samun; Grace, Delia; Samad, Mohammed Abdus; Lindahl, Johanna F. (Frontiers in Sustainable Food Systems, 2023)
Contamination with heavy and toxic metals along the food value chain is a public health concern in Bangladesh. In this study, 608 fish and chicken samples from traditional and modern retail outlets in urban, peri-urban, and rural areas were collected and analyzed for chromium (Cr), cadmium (Cd), and lead (Pb) contamination, using atomic absorption spectrometry method. The daily intake, target hazard quotient and the target carcinogenic risk (for lead only) as a result of fish and chicken consumption was calculated based on mean results, as well as by Monte Carlo simulation in @Risk with 100,000 iterations (quantitative risk assessment). Cr and Cd were detected in 80-86% of both chicken meat and fish samples, while prevalence of Pb found in chicken meat and fish was 54.9 and 23.3%, respectively. The mean concentration (±SD) of Cr, Cd, and Pb in chicken meat were 0.66±0.93, 0.02±0.03, and 0.09±0.10 mg/kg, respectively; and in fish were 0.49±0.62, 0.02±0.03, and 0.06±0.09 mg/kg, respectively. The estimated daily intakes of Cr, Cd and Pb from chicken and fish were lower than the maximum tolerable daily intake in all studied areas. In addition, the target carcinogenic risk for Pb in chicken was lower than the negligible range indicating the risk of cancer due to exposure to Pb through chicken meat and fish consumption was very low. The present study concludes that consumption of chicken meat and fish in Bangladesh, currently at very low levels, is unlikely to constitute a major health risk for humans in respect to these metals. However, continuous market surveillance for heavy metals in food stuff is recommended, especially since consumers may increase their meat intake.